Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve for the right-hand limit of the function [tex]\( f(x) = \frac{x^2 + 2x - 3}{x - 1} \)[/tex] as [tex]\( x \)[/tex] approaches 2, let's go through the steps methodically.
1. First, understand the function:
The function given is [tex]\( f(x) = \frac{x^2 + 2x - 3}{x - 1} \)[/tex].
2. Simplify the function if possible:
We notice that the numerator [tex]\((x^2 + 2x - 3)\)[/tex] can be factored. Let's factor it:
[tex]\[ x^2 + 2x - 3 = (x + 3)(x - 1) \][/tex]
So the function becomes:
[tex]\[ f(x) = \frac{(x + 3)(x - 1)}{x - 1} \][/tex]
For [tex]\( x \neq 1 \)[/tex], we can cancel the [tex]\((x - 1)\)[/tex] terms in the numerator and the denominator:
[tex]\[ f(x) = x + 3 \quad \text{for} \quad x \neq 1 \][/tex]
3. Determine the limit:
Now, we need to find the right-hand limit as [tex]\( x \)[/tex] approaches 2 of the simplified function [tex]\( f(x) = x + 3 \)[/tex].
[tex]\[ \lim_{{x \to 2^+}} (x + 3) \][/tex]
4. Evaluate the limit:
Plug in [tex]\( x = 2 \)[/tex] into the simplified function:
[tex]\[ \lim_{{x \to 2^+}} (x + 3) = 2 + 3 = 5 \][/tex]
Thus, the right-hand limit of the function [tex]\( f(x) = \frac{x^2 + 2x - 3}{x - 1} \)[/tex] as [tex]\( x \)[/tex] approaches 2 is [tex]\( 5 \)[/tex].
So, the correct answer is:
D. 5
1. First, understand the function:
The function given is [tex]\( f(x) = \frac{x^2 + 2x - 3}{x - 1} \)[/tex].
2. Simplify the function if possible:
We notice that the numerator [tex]\((x^2 + 2x - 3)\)[/tex] can be factored. Let's factor it:
[tex]\[ x^2 + 2x - 3 = (x + 3)(x - 1) \][/tex]
So the function becomes:
[tex]\[ f(x) = \frac{(x + 3)(x - 1)}{x - 1} \][/tex]
For [tex]\( x \neq 1 \)[/tex], we can cancel the [tex]\((x - 1)\)[/tex] terms in the numerator and the denominator:
[tex]\[ f(x) = x + 3 \quad \text{for} \quad x \neq 1 \][/tex]
3. Determine the limit:
Now, we need to find the right-hand limit as [tex]\( x \)[/tex] approaches 2 of the simplified function [tex]\( f(x) = x + 3 \)[/tex].
[tex]\[ \lim_{{x \to 2^+}} (x + 3) \][/tex]
4. Evaluate the limit:
Plug in [tex]\( x = 2 \)[/tex] into the simplified function:
[tex]\[ \lim_{{x \to 2^+}} (x + 3) = 2 + 3 = 5 \][/tex]
Thus, the right-hand limit of the function [tex]\( f(x) = \frac{x^2 + 2x - 3}{x - 1} \)[/tex] as [tex]\( x \)[/tex] approaches 2 is [tex]\( 5 \)[/tex].
So, the correct answer is:
D. 5
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.